A monument to whom? Artist positionality in community art-based projects. Issue 131 (May 2022) - Tartari, Maria; Trimarchi, Marianna; Ghirardi, Sendy; Luigi Sacco, Pier
Highlights: We compare Foucaultian vs. Lefebvrian heterotopias as an analytical approach to community-based art projects. We study Hirschhorn's Monument to Gramsci as a test case study for our approach. We critically discuss artist positionality and deontological responsibility of artistic agency. We assess the consequences on marginal communities of top-down hegemonic artistic agency. Abstract: Artistic interventions in the public domain are often legitimized as opportunities for the empowerment of local communities. However, the nature of such interventions is complex and cannot be inferred from stated intentions. The interaction between agents of cultural and artistic interventions and local communities is shaped by power relationships that are seldom made explicit, let alone negotiated. Here, we analyze The Gramsci Monument, a site-specific project by Thomas Hirschhorn that took place in the Forest House neighborhood (Bronx, New York) in 2013. The project has been celebrated as an example of an emancipatory practice that involved a disenfranchised local community. We show that it could be rather taken as an example of how art-driven space domestication may lead to forms of alienation and paternalism without actual sharing of creative responsibility and negotiation with the local community. We analyze the implications of this practice through a conceptual framework of artist positionality and deontological responsibility of artistic agency.